Long-range transport of air pollution into the Arctic - Stohl, A.; Berg, T.; Breivik, K.; Burkhardt, J.F.; Eckhardt, S.; Fjæraa, A.; Forster, C.; Herber, A.; Lunder, C.; McMillan, W.W.; Manø, S.; Oltmans, S.; et al. (2007)
This paper presents an overview of air pollution transport into the Arctic. The major transport processes will be highlighted, as well as their seasonal, interannual, and spatial variability. The source regions of Arctic air pollution will be discussed, with a focus on black carbon (BC) sources, as BC can produce significant radiative forcing in the Arctic. It is found that Europe is the main source region for BC in winter, whereas boreal forest fires are the strongest source in summer, especially in years of strong burning. Two case studies of recent extreme Arctic air pollution events will be presented. In summer 2004, boreal forest fires in Alaska and Canada caused pan-Arctic enhancements of black carbon. The BC concentrations measured at Barrow (Alaska), Alert (Canada), Summit (Greenland) and Zeppelin (Spitsbergen) were all episodically elevated, as a result of the long-range transport of the biomass burning emissions. Aerosol optical depth was also episodically elevated at these stations, with an almost continuous elevation over more than a month at Summit. During the second episode in spring 2006, new records were set for all measured air pollutant species at the Zeppelin station (Spitsbergen) as well as for ozone in Iceland. At Zeppelin, BC, AOD, aerosol mass, ozone, carbon monoxide and other compounds all reached new record levels, compared to the long-term monitoring record. The episode was caused by transport of polluted air masses from Eastern Europe deep into the Arctic, a consequence of the unusual warmth in the European Arctic during the episode. While fossil fuel combustion sources certainly contributed to this episode, smoke from agricultural fires in Eastern Europe was the dominant pollution component. We also suggest a new revolatilization mechanism for persistent organic pollutants (POPs) stored in soils and vegetation by fires, as POPs were strongly elevated during both episodes. All this suggests a considerable influence of biomass burning on the pollutant concentrations in the Arctic in ...